Advanced Technologies for the Optimization of Internal Combustion Engines - Cinzia Tornatore (MDPI AG, 2021)
Even in a scenario where electric vehicles gain market share and the sale of internal combustion engines is gradually reduced, at the present time, there are still no real options that can totally replace the internal combustion (IC) engine over the entire range of its applications [...]